THE ESSENTIAL OF REALIA: ESTABLISHING STUDENTS’ WRITING ABILITY TO THE REAL WORLD - Rosdiana (English Education Department, 2017)
Realia is a term for real things or concrete objects that are used in the classroom to build background knowledge and vocabulary. The purpose of this study is to describe: (1) students achievment in writing a descriptive paragraph using realia media for the second grade students of English department of STKIP BBG., (2) students’ ability in learning to write a descriptive paragraph with realia media. The design used in this research is descriptive qualitative research. The subject of this research is English department students of STKIP BBG consist of 25 students. The method used in collecting data is through observation and test. The data analysis used in this study is qualitative and quantitative descriptive. The results show that (1) Learning to write paragraph description with mind mapping model by teacher is in accordance with existing theory. (2) The ability of second grade students of English department in writing the descriptive paragraph is quite good. The scores obtained are 78.13. Although the scores obtained have reached the good category, it seems that teacher performance needs to be improved again by providing more intensive exercises, both in making mind mapping and development into paragraphs, to achieve maximum results.